Granuloma formation following cyanoacrylate glue injection in peripheral veins and arteriovenous malformation. (March 2020) - Parsi, Kurosh; Kang, Mina; Yang, Anes; Kossard, Steven
Background: Cyanoacrylate adhesive closure is a technically simple alternative to endothermal ablation of peripheral veins. N-butyl cyanoacrylate is delivered via catheters or by percutaneous injection resulting in occlusion of target veins. The local tissue reaction or the systemic immune response that may follow have not been characterised. Aim: To characterise the late local tissue reaction to N-butyl cyanoacrylate glue injected in peripheral vessels. Methods: Biopsies were obtained from two patients. In patient one, distal tributaries of the great saphenous vein were injected with VenaBlock™ glue under ultrasound guidance. Ultrasound-guided incisional biopsies were performed at one week, six weeks and 12 months. In patient two, a peripheral arterio-venous malformation was injected with Venablock™ and biopsy was performed 12 months later. Histological analysis was performed using haematoxylin and eosin and immunofixation with CD-4, CD-31, CD-34, CD-68 and D2-40. Results: Echogenic material with a strong shadow artefact consistent with the injected N-butyl cyanoacrylate was observed on ultrasound on all follow-up occasions. Biopsies taken at one week showed intravascular glue without histiocytes. Biopsies at six weeks showed isolated foreign body histiocytes coating intravascular fibrillary glue spicules but no granuloma formation. The one-year biopsies showed extravascular changes including fibrosis, lymphoid aggregates and multiple extravascular foreign body cavitated granulomas. Some vessel lumens contained residual spicules of glue but no intravascular granulomas. The extravascular granulomas were deeply located, asymptomatic and not complicated by clinical ulceration. Histologically, there was no evidence of transepidermal elimination. Conclusion: Extravascular foreign body cavitated granulomas containing spicules of glue with fibrosis and lymphoid aggregates occur as a delayed finding following the use of N-butyl cyanoacrylate.